Morphological Confirmation Of Probasidium For Laurobasidium Hachijoense Comb. Nov. Proposed By The Molecular Analysis - Hideyuki, Nagao; Kakishima, Makoto (2017)
Basidia are evidently formed inside the galls not on the surface.L.hachijoense has probasidium and its basidium emerged from probasidium.No clamp was observed